2015
DOI: 10.1186/s12885-015-1038-y
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy for stage III colon cancer: relative dose intensity and survival among veterans

Abstract: Background: Given the paucity of information on dose intensity, the objective of this study is to describe the use of adjuvant chemotherapy for stage III colon cancer, focusing on relative dose intensity (RDI), overall survival (OS) and disease-free survival (DFS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 30 publications
4
80
1
3
Order By: Relevance
“…Yet, many patients still experience severe toxicity and are subsequently dose-reduced, delayed or discontinue treatment prematurely. Discontinuation, reductions and delays in chemotherapy can reduce overall and recurrence-free survival, 3 making individualized dosing a priority. Body composition, the amount and distribution of adipose and lean soft tissue (the main compartment of which is skeletal muscle mass) is one factor influencing the pharmacokinetics and metabolism of many chemotherapy agents.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, many patients still experience severe toxicity and are subsequently dose-reduced, delayed or discontinue treatment prematurely. Discontinuation, reductions and delays in chemotherapy can reduce overall and recurrence-free survival, 3 making individualized dosing a priority. Body composition, the amount and distribution of adipose and lean soft tissue (the main compartment of which is skeletal muscle mass) is one factor influencing the pharmacokinetics and metabolism of many chemotherapy agents.…”
Section: Introductionmentioning
confidence: 99%
“…Aspinall et al . reported that a relative dose intensity of 5‐FU/LV of less than 70% was associated with worse 5‐year OS for Stage III patients, and Neugut et al . reported that 5‐FU‐based chemotherapy for Stage III patients over 5–7 months was associated with better 5‐year OS than the same regimen for 1–4 months .…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that keeping the relative dose intensity (RDI) high is important in adjuvant chemotherapy [11][12]. For instance, in adjuvant chemotherapy with cyclophosphamide, methotrexate, and fluorouracil for breast cancer, maintaining RDI ≥85% is recommended to prolong the relapse-free survival and overall survival [11].…”
Section: Ivyspringmentioning
confidence: 99%
“…For instance, in adjuvant chemotherapy with cyclophosphamide, methotrexate, and fluorouracil for breast cancer, maintaining RDI ≥85% is recommended to prolong the relapse-free survival and overall survival [11]. Likewise, in colon cancer, RDI of adjuvant chemotherapy is known to affect the prognosis [12]. As with breast and colon cancer, keeping high RDI is expected to improve the prognosis in NSCLC patients treated with adjuvant CV therapy.…”
Section: Ivyspringmentioning
confidence: 99%